2015
DOI: 10.1016/j.apsusc.2014.12.165
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition from ZnS and Cu2SnS3 multicomponent targets

Abstract: Thin films of ZnS and Cu 2 SnS 3 have been produced by pulsed laser deposition (PLD), the latter for the first time. The effect of fluence and deposition temperature on the structure and the transmission spectrum as well as the deposition rate has been investigated, as has the stoichiometry of the films transferred from target to substrate. Elemental analysis by energy dispersive X-ray spectroscopy indicates lower S and Sn content in Cu 2 SnS 3 films produced at higher fluence, whereas this trend is not seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The observation was related to the possible vaporization of small drops during film growth. Droplets with dimensions ranging from hundreds of nanometers up to one micron have been observed on surfaces films synthesized by pulsed laser deposition route [39]. The observed grain size is higher than crystallite size calculated from XRD results using Scherrer equation.…”
Section: Morphological Propertiesmentioning
confidence: 96%
“…The observation was related to the possible vaporization of small drops during film growth. Droplets with dimensions ranging from hundreds of nanometers up to one micron have been observed on surfaces films synthesized by pulsed laser deposition route [39]. The observed grain size is higher than crystallite size calculated from XRD results using Scherrer equation.…”
Section: Morphological Propertiesmentioning
confidence: 96%
“…Thin CTS films have been made using several techniques, spin coating [21][22][23][24], pulsed laser deposition from Cu 2 SnS 3 mulitcomponent targets [25]; doctor blade method [26] nano ink [27]; spray pyrolysis [28,30]; direct liquid coating [31,32]; sulfurizing Cu/Sn stacked precursors deposited on glass substrates by electron beam & H. Dahman h_dahman_2000@yahoo.com evaporation [33], sulfurizing, (Cu, Sn)S structured precursors prepared by successive ionic layer absorption and reaction (SILAR) [34,35]; annealing in sulphur atmosphere electrodeposited metals [18,36]; heat treatment of electrodeposited SnS-Cu layers [37], sulfurization of DC magnetron sputtered Sn-Cu stacks [38][39][40][41], direct evaporation of a synthesized Cu 2 SnS 3 powder [42], three steps method based on sulfurization of evaporated copper on sprayed SnS 2 film [43], sulfurization of a stack of vacuum-evaporated Cu and Sn films [44][45][46] route earlier used by Rezig and Dahman to prepare thin films of iron pyrite [47,48]. In this study, pure cubic structure Cu 2 SnS 3 films were grown by simple one-step spin coating technique from a single precursor's solution of Cu-Sn-thiourea complex.…”
Section: Introductionmentioning
confidence: 99%
“…The highest efficiency of CTS solar cells of 4.65 % was achieved by thermal evaporation [7]. CTS thin films have also, more recently, been fabricated by pulsed laser deposition (PLD) [8]. Vanalakar et al [9] have reported on the first CTS solar cell prepared by pulsed laser deposition with an efficiency of 0.82%.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of droplets (in some papers called particulates) in the growing films is a well-known problem, which can be addressed in a number of ways [11]. Particularly, droplets up to 1 micron in diameter or larger were observed in the films of CTS deposited by PLD [8,9]. The influence of droplets on the overall efficiency of the solar cell is not well understood, but it is clear that it can be detrimental for the cell performance for the following reasons: i) the droplet size can be larger than the overall thickness of the absorber layer, resulting in a rough interface and possible shunt paths between the CTS film and subsequent solar cell layers [12]; and ii) the droplets can have a different composition than the matrix of the CTS film [13,14], resulting in non-homogeneity in composition and therefore different charge carrier transport properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation